Algoritma Backtracking Pada Perjalanan Pulang Robot Pemadam Api - Arya Sukma Krisnayoga; Yoga Divayana; Pratolo Rahardjo (Program Studi Teknik Elektro UNUD, 2019)
Kontes Robot Pemadam Api Indonesia or commonly in short KRPAI is a robot competition that has the main mission of putting out fires. During the competition there are several bonus points that must be taken. One bonus that must be taken is the robot able to return home after holding a fire. In this research the KRPAI Udayana University robot will use the backtracking algorithm to return home. The purpose of using backtracking alogritma is to shorten the distance back home to the robot. In KRPAI University robot Udayana use SRF-05 sensors to measure the distance of the robot to the wall and use 18 servo as the driving leg of the robot. the use of backtracking algorithm, the path that has been passed by the robot when looking for fire will be simplified. the results of the simplification of the fire search path will be used as the return route. Based on the test results, using the robot backtracking algorithm is able to minimize the distance traveled when returning home, the room entered is only 1 room, and there is no detecting dolls.